Analisis Kualitas Pelayanan Tax Survey dalam Pemutakhiran Data PBB – P2 - I Gusti Ayu Putu Suharyati; Nyoman Diah Utari Dewi; Luh Riniti Rahayu (Penerbit Goodwood, 2023)
Purpose: Urban and rural land and building tax (PBB-P2) is one of the contributors to local revenue. The existing PBB-P2 data is not necessarily accurate so it is necessary to update the data through the Tax survey program and to realize this, the quality of service from employees is needed. to describe the quality, factors that hinder and efforts that can be made to improve service quality. Research methodology: The research method uses qualitative research with data collection techniques of interviews. Analysis techniques using descriptive analysis. Results: The quality of employee services in the form of employee service quality is still not optimal and the factors that hinder the quality of PBB - P2 data updating services based on Tax survey are supporting facilities and infrastructure, low socialization, lack of human resources and administrative problems. The efforts made in improving service quality are to make SOPs for updating data using Tax survey and simplifying requirements, completing supporting facilities and infrastructure at BPKPD, increasing the Capacity Ability and Expertise of BPKPD HR, conducting performance appraisals and giving rewards to officers, and conducting Internal Supervision to officers. Limitations: This research is still analyzed descriptively and only uses a few informants. Contribution: This research is expected to provide additional information or input in improving the quality of technology-based tax update services in the form of a Tax survey system at BPKPD.